Calculations of thermal radiation transfer of C2H2 and C2H4 together with H2O, CO2, and CO in a one-dimensional enclosure using LBL and SNB models. (August 2017) - Qi, Chaobo; Zheng, Shu; Zhou, Huaichun
Abstract: Generally, the involvement of hydrocarbons such as C2 H4 and its derivative C2 H2 in thermal radiation has not been accounted in the numerical simulation of their flames, which may cause serious error for estimation of temperature in the early stage of combustion. At the first, the Statistical Narrow-Band (SNB) model parameters for C2 H2 and C2 H4 are generated from line by line (LBL) calculations. The distributions of the concentrations of radiating gases such as H2 O, CO2, CO, C2 H2 and C2 H4, and the temperature along the centerline of a laminar ethylene/air diffusion flame were chosen to form a one-dimensional, planar enclosure to be tested in this study. Thermal radiation transfer in such an enclosure was calculated using the LBL approach and the SNB model, most of the relative errors are less than 8% and the results of these two models shows an excellent agreement. Below the height of 20 mm, which is the early stage of the flame, the average fraction contributed by C2 H2 and C2 H4 in the radiative heat source is 33.8%, while that by CO is only 5.8%. This result indicates that the involvement of C2 H2 and C2 H4 in radiation heat transfer needs to be taken into account in the numerical modeling of the ethylene/air diffusion flame, especially in the early stage of combustion. Highlights: The SNB parameters of C2 H2 and C2 H4 are generated based on HITRAN2012 database. Radiation transfer by C2 H2 and C2 H4 in the flame are estimated in a 1-D enclosure. C2 H2 and C2 H4 contribute 33.8% of the radiative source in the flame below 20 mm.